Sistem Informasi Penyewaan Gedung Serbaguna Desa Meteseh Berbasis Web Guna Meningkatkan Aksesibilitas & Efisiensi Penyewaan untuk Masyarakat Desa - Alfia Siska Nur Safitri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) - Institut Teknologi dan Bisnis Semarang, 2024)
This research aims to increase efficiency in the building reservation process and facilitate information accessibility for village communities. This research focuses on optimizing the rental of the Meteseh Village Multipurpose Building (GSG) through the development of a web-based information system. The existence of a Multipurpose Building is vital for local community activities, such as meetings, arts events, sports, traditional ceremonies and other activities. Using qualitative research methods, data was collected using observation techniques, interviews with the Head of Meteseh Village who is responsible for building management, and literature studies to provide a strong basis for system development In this designed system, the author uses the Waterfall method as a development and modeling using the Unified Modeling Language (UML). The system design stage involves creating system flow and database design. In this web design, the author uses HTML and CSS programming languages for the user interface, as well as Javascript and Firebase for database processing. The results of this research are in the form of a rental booking website for the Meteseh Village Multipurpose Building. Implementing this information system can help improve the building management process and make it easier for the public to access information and make building reservations.